Biomassa Kerang Anadara granosa pada Perairan Pantai Kabupaten Indragiri Hilir - Nasution, Syafruddin (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2009)
The present study was carried out to investigate the biomass of cockle (Anadara granosa) from coastal waters ofSouth Indragiri District, Riau Province. The biomass was investigated by quadrad sampling method in the intertidalarea along the Concong beach, where fishing of cockles mainly occured. The first station was near by the Concongestuary, while the second station was about 3 miles away from the fisrt one. Samples were collected from threedifferent portions of the intertidal zone that of High Intertidal Mid-Intertidal, and Low Intertidal. The result showedthat the highest biomass was found at the lower partion of the intertidal zone. Soft tissue of A. granosa was about24.8% of total wet-weight and 7.2 % of dry-weight. While material organic was about 85 % of soft tissue dry-weight.Water qualities of the sampling station showed that the overall water qualities were still in normal condition.